PANDANGAN FIQIH MUNAKAHAT TERHADAP PERKAWINAN ADAT SUKU SASAK LOMBOK TIMUR - Said, Purwadi; Wibowo, Muhammad Kurniawan Budi; Baehaqi, B (AL HUKMU: Journal of Islamic Law and Economics, 2023)
The purpose of this study is to explain the views of the Munakahat Fik people on Sasak traditional marriages in the area of the Department of Religion, Pringabya District, East Lombok. It then describes the traditions of the Meralik tribe of the Sasak tribe of East Lombok. In this case, the subject of the survey is the Sasak people of East Lombok Island, and the subject of the survey is their view of Islam using a qualitative method. As a result of the study, the authors concluded that the Meralik tradition of the Sasak people of Lombok in the Pringabaya district of the East Lombok Religious Affairs Authority (KUA) consists of several stages. (1) Middle. (Visits her future wife in front of the house) Here there is an agreement between the two parties to kidnap her wife or have her husband take her away. (2) The man must kidnap (run away) the bride. (3) The man must report the elopement to the chief of the village where the bride lives, the so-called Serval. (4) Payment of deposit and dowry money. (5) Conducting weddings in Islamic style. (6) A type of marriage payment common among the Sasak people of Lombok is called Sorong Sera. (7) Nyongkolan, a women's accompaniment to her family and strolling through the village to traditional Lombok music. The correct practice of melalik is very legal in terms of legality since in melalik the conditions and pillars are fulfilled according to Islamic law. Apart from what is not justified, namely the process of marriage proposal, the process of marriage proposal in the melalik tradition in Islam is very different and this tradition can be harmful.